2015
DOI: 10.1007/s40069-015-0118-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wet Curing Duration on Long-Term Performance of Concrete in Tidal Zone of Marine Environment

Abstract: A proper initial curing is a very simple and inexpensive alternative to improve concrete cover quality and accordingly extend the service life of reinforced concrete structures exposed to aggressive species. A current study investigates the effect of wet curing duration on chloride penetration in plain and blended cement concretes which subjected to tidal exposure condition in south of Iran for 5 years. The results show that wet curing extension preserves concrete against high rate of chloride penetration at e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The curve fitting has been done so that the chloride profiles are fitted where the correlation between the measured and fitted profiles has a maximum. Curve fitting has been performed following a procedure described in NordTest NT Build 443 and resulted in two regression parameters; a diffusion coefficient and surface chloride content [7]. Besides Fick's diffusion equation analysis method, there are some diffusion equation analysis methods such as Szweda's equation which is based on the expression determining the diffusion coefficient of chloride ions D 1 =1/Q − which is the reverse of the diffusion resistance of the entire tested concrete zone [9], Nernst-Einstein equation for porous materials such as concrete the diffusion coefficient formulation [10], Nernst-Planck equation numerical model based on the ionic coupling effects among ions in chloride solutions and ions in concrete pore solution, Na+, K+, OH- [11] and Bayesian inverse technique is used to estimate diffusion and migration coefficients of chloride in concrete treated as a saturated porous material [12].…”
Section: Analysis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The curve fitting has been done so that the chloride profiles are fitted where the correlation between the measured and fitted profiles has a maximum. Curve fitting has been performed following a procedure described in NordTest NT Build 443 and resulted in two regression parameters; a diffusion coefficient and surface chloride content [7]. Besides Fick's diffusion equation analysis method, there are some diffusion equation analysis methods such as Szweda's equation which is based on the expression determining the diffusion coefficient of chloride ions D 1 =1/Q − which is the reverse of the diffusion resistance of the entire tested concrete zone [9], Nernst-Einstein equation for porous materials such as concrete the diffusion coefficient formulation [10], Nernst-Planck equation numerical model based on the ionic coupling effects among ions in chloride solutions and ions in concrete pore solution, Na+, K+, OH- [11] and Bayesian inverse technique is used to estimate diffusion and migration coefficients of chloride in concrete treated as a saturated porous material [12].…”
Section: Analysis Methodsmentioning
confidence: 99%
“…-CP V RS [26], -w/c = 0.55 and 0.65 [11] -w/c = 0.32 [12] -OPC, HES, SCB*AL cement [3] -OPC, CEM I and CEM III/A [27] -w/c = 0,4 [28] -w/c = 0.4 -0.5 [29] -w/c = 0.30, 0.35, 0.40 and 0.45 [30] -PC equivalent to ASTM Type II [7] -w/c = 0.5 [31] [27] [7] -CEM I 42.5 N [24] -w/c = 0.55, 0.50, and 0.45 [25] -CEM IV/A-P 42.5R, CEM II/A-L 42.5R, and CEM III/A 42.5R [25] Water/Binder (W/B) ratio: Aggregate/cement ratios: 4 -6 [26] -W/B = 0.5 [3] -W/B = 0.4, 0.5, and 0.6 [5] Fly ashbinder ratios: 0.2, 0.35, and 0.5 [3] -W/B = 35%, 45%, 55% [15], -W/B = 0.47 [18] The volume fractions of coarse aggregate: -W/B = 0.4 and, 0,33 [24] -v = 0, 0.2, 0.3, 0.4, and 0.5. [15]…”
Section: Various Materials Used In Concrete Specimensmentioning
confidence: 99%
“…Several research have reported the durability of concrete structures in the marine environment, including long-term investigation of concrete performance exposed to seawater [3][4][5][6]. Furthermore, concrete mixed with seawater achieved a good mechanical properties performance even though it was slightly lower than those using plain water [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Concrete structures face many threats to their service life. A number of durability problems are caused by external fluids penetrating into cement-based materials [1][2][3][4]. These fluids can contain potentially harmful ionic species, can lead to damage from corrosion, sulfate attack, alkali silica reaction, bulk freeze thaw, and salt scaling [5][6].…”
Section: Introductionmentioning
confidence: 99%